2017
DOI: 10.1007/s10973-017-6348-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotalcite-derived Co-containing mixed metal oxide catalysts for methanol incineration

Abstract: The Co-Mg-Al mixed metal oxides were prepared by calcination of co-precipitated hydrotalcite-like precursors at various temperatures (600-800°C), characterised with respect to chemical (AAS) and phase (XRD) composition, textural parameters (BET), form and aggregation of cobalt species (UV-vis-DRS) and their redox properties (H 2 -TPR, cyclic voltammetry). Moreover, the process of thermal decomposition of hydrotalcite-like materials to mixed metal oxide systems was studied by thermogravimetric method combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Characteristic diffraction lines occurring at approximately 21,35,41,43,50,63,67,74,78,85 and 88 °2θ were ascribed to spinel-like phases labelled as: (Cu,Mg)Fe2O3 (ICDD PDF-2 card No 01-076-9731). As expected [14,18,33], high temperature of calcination (800 °C) favors the formation of complex oxide structures; therefore, these patterns were observed for each sample irrespective of the copper loading. Apart from the complex spinel phases, characteristic diffraction lines for simple oxides like periclase (MgO) and tenorite (CuO) were also found.…”
Section: Chemical Compositionsupporting
confidence: 73%
See 1 more Smart Citation
“…Characteristic diffraction lines occurring at approximately 21,35,41,43,50,63,67,74,78,85 and 88 °2θ were ascribed to spinel-like phases labelled as: (Cu,Mg)Fe2O3 (ICDD PDF-2 card No 01-076-9731). As expected [14,18,33], high temperature of calcination (800 °C) favors the formation of complex oxide structures; therefore, these patterns were observed for each sample irrespective of the copper loading. Apart from the complex spinel phases, characteristic diffraction lines for simple oxides like periclase (MgO) and tenorite (CuO) were also found.…”
Section: Chemical Compositionsupporting
confidence: 73%
“…Higher temperatures of calcination promote the formation of more thermally stable species and reorganization of the already existing structures into more complex ones. In the case of samples modified by Ce (800-Cu-Mg-Fe-O-Ce), the XRD patterns exhibit additional characteristic diffraction lines at positions 33,38,45,55,66,70 and 82 • 2θ related to CeO 2 phase (ICDD PDF-2 card No 01-080-5548). The lines characteristic for individual oxide species are at the same positions irrespective of the copper amount or Ce intercalation, which means that all samples are characterized by a similar cell parameter of individual phases a = 0.84 nm for MgFe 2 O 4 , a = 0.42 nm for MgO, a = 0.47 nm, b = 0.34 nm, c = 0.51 nm for CuO and a = 0.51 nm for CeO 2 oxide.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Then, at immediately higher temperatures, the lamellae dehydroxylation begins to occur, which largely depends on the individual thermal stability of the metal hydroxides present in the material (Puttaswamy e Kamath, 1997) This stage can extend up to over 400 ºC, depending on the composition, and can accelerate the last stage of decomposition, which is interlayer decarbonation. Depending on the composition, hydrotalcite structures not yet decarbonated can be regenerated by hot rehydration, since the anchoring of the carbonate anion gives structural memory to hydrotalcite (Basag et al, 2017;Rhee e Kang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Different factors are strongly related to the catalytic performance of HT derived materials. The performance of HT derived catalyst mostly depends on its preparation procedure [14] [15] [16] [17] [18], pore size [19], total surface area [20] [21] [22], modification [23] [24] [25] [26], types of metal constituents [18] [27] [28], composition [1] [29] [30] [31], promoters [32] [33] [34] [35], operating temperature [36]. Different metallic oxides prepared by HT precursors have shown super catalytic performance during fuel processing [5] [6] [14] [28] [36] [37] [38] [39] [40].…”
Section: Introductionmentioning
confidence: 99%
“…This redesign can be done by being adjusted the M i and M ii metal ions as well as their ratio [41] [43] [44] [45] [46] [47]. Basąg et al, [18] reported that the performance of HT derived catalyst obtained at higher temperatures. In the last decades, a number of efforts have been taken where the focuses on highly stable and active catalysts.…”
Section: Introductionmentioning
confidence: 99%